2006
DOI: 10.1002/ajhb.20581
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and interobserver error of digit ratio (2D:4D) measurements made by experts

Abstract: The second-to-fourth digit ratio (2D:4D) is sexually differentiated (lower in men than in women), a likely biomarker for organizational (permanent) effects of prenatal testosterone, and a correlate of many sex-dependent, hormonally influenced traits and phenotypes. The extent of 2D:4D measurement repeatability across different research groups is unknown. This study assessed the repeatability and interobserver error of 2D:4D measurements made by 17 experts (researchers who have contributed to the 2D:4D literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
101
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 135 publications
(109 citation statements)
references
References 14 publications
8
101
0
Order By: Relevance
“…However, we are unable to locate any study that supported similar levels of interobserver agreement when determining 2D:4D from photocopied and printed hand scans. Although the level of agreement we reported for 2D:4D derived from printed scans was similar to findings made by Voracek et al (2007), the reliability coefficients were lower than those observed for photocopies and computerassisted image analysis. In our current study, we believe printed scanned images yielded less reliable 2D:4D because image quality was significantly lost at the time of printing-this occurred despite images being printed at the highest quality available to us (i.e., 600 dpi).…”
supporting
confidence: 77%
See 3 more Smart Citations
“…However, we are unable to locate any study that supported similar levels of interobserver agreement when determining 2D:4D from photocopied and printed hand scans. Although the level of agreement we reported for 2D:4D derived from printed scans was similar to findings made by Voracek et al (2007), the reliability coefficients were lower than those observed for photocopies and computerassisted image analysis. In our current study, we believe printed scanned images yielded less reliable 2D:4D because image quality was significantly lost at the time of printing-this occurred despite images being printed at the highest quality available to us (i.e., 600 dpi).…”
supporting
confidence: 77%
“…While each of the commonly used methods of acquiring 2D:4D is generally validated within studies to show they yield highly repeatable measurements among a single observer, it must be acknowledged that we know very little about the reliability of 2D:4D measurements made by multiple observers using a single technique (Voracek et al, 2007) or the reliability of measurements made by the same observers using multiple techniques (Kemper and Schwerdtfeger, in press;Manning et al, 2005 , 2005). These findings may be interpreted to mean that 2D:4D are technique dependent and this has serious implications for a field that necessitates a highly precise tool to identify relatively small differences in 2D:4D among study populations (Kemper and Schwerdtfeger, in press).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Measurements of digit ratio from photographs or scans are the most accurate methods (Manning, 2002;Voracek et al, 2007;Kemper and Schwerdtfeger, 2009;Ruuskanen et al, 2011) are difficult to use in the field (Manning, 2002;Navarro et al, 2007;Dreiss et al, 2008). On the front fore and hind limbs of newts there is no visible basal crease; thus, we had to create a standardized method of digits measurement.…”
Section: Discussionmentioning
confidence: 99%